The Influence of Gadgets on Children's Development - Adinda Dwi Maharani; Annisaul Khairat (AGENDA: Jurnal Analisis Gender dan Agama, 2023)
The current development of science and technology is advancing rapidly. The influence of gadgets is substantial. This influence doesn't only affect adults, but also children, especially students. Of course, the use of gadgets brings about both positive and negative impacts. This research aims to examine the effects of gadget usage on the development of children's character, particularly focusing on their religious character and obedience. The method utilized in this study is descriptive quantitative, utilizing survey results obtained from online surveys conducted among students of SD 014 Perawang Barat and SMPN 02 Minas. Based on the research findings, it can be concluded that gadget usage significantly influences the development of students. It has a positive impact when used appropriately for educational and positive purposes, under parental supervision. However, it can have negative consequences if used inappropriately, as a result of lack of parental supervision.